2021
DOI: 10.37213/cjal.2021.31338
|View full text |Cite
|
Sign up to set email alerts
|

Does Portfolio-Based Language Assessment Align with Learning-Oriented Assessment? Evidence from Literacy Learners and their Instructors

Abstract: A high-stakes Portfolio-Based Language Assessment (PBLA) protocol that was fully implemented in all Language Instruction for Newcomers to Canada (LINC) programs in 2019 requires instructors and students to set language-learning goals and complete, compile, and reflect on numerous authentic language tasks. Due to the language barriers incurred when communicating with beginner English-as-a-second-language literacy learners (BELLs), no PBLA research has been conducted with BELLs. To address this gap, we interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Teachers reported that the formal portfolio assessment that was implemented in their context caused stress for the learners. Learners agreed that the assessments caused stress, but still reported to find the portfolio useful for their learning (Abbott et al, 2021). The results indicate that a portfolio might be a useful tool for the LESLLA practice.…”
Section: Introductionmentioning
confidence: 80%
“…Teachers reported that the formal portfolio assessment that was implemented in their context caused stress for the learners. Learners agreed that the assessments caused stress, but still reported to find the portfolio useful for their learning (Abbott et al, 2021). The results indicate that a portfolio might be a useful tool for the LESLLA practice.…”
Section: Introductionmentioning
confidence: 80%